Hollow carbon sphere/metal oxide nanocomposites anodes for lithium-ion batteries - Wenelska, Karolina; Ottmann, Alexander; Thauer, Elisa; Klingeler, Rüdiger (Energy, 2016)
HCS (Hollow carbon spheres) covered with metal oxide nanoparticles (SnO2 and MnO2, respectively) were successfully synthesized and investigated regarding their potential as anode materials for lithium-ion batteries. Raman spectroscopy shows a high degree of graphitization for the HCS host structure. The mesoporous nature of the nanocomposites is confirmed by Brunauer-Emmett-Teller analysis. For both metal oxides under study, the metal oxide functionalization of HCS yields a significant increase of electrochemical performance. The charge capacity of HCS/SnO2 is 370 mA hg−1 after 45 cycles (266 mA hg−1 in HCS/MnO2) which clearly exceeds the value of 188 mA hg−1 in pristine HCS. Remarkably, the data imply excellent long term cycling stability after 100 cycles in both cases. The results hence show that mesoporous HCS/metal oxide nanocomposites enable exploiting the potential of metal oxide anode materials in Lithium-ion batteries by providing a HCS host structure which is both conductive and stable enough to accommodate big volume change effects.
Gesehen am 18.06.2020